Transcriptome Profile Analysis on Ovarian Tissues of Autotetraploid Fish and Diploid Red Crucian Carp - Wang, Yude; Zhang, Minghe; Qin, Qinbo; Peng, Yajun; Huang, Xu; Wang, Chongqing; Cao, Liu; Li, Wuhui; Tao, Min; Zhang, Chun; Liu, Shaojun (Frontiers in Genetics, 2019)
Polyploidization can significantly alter the size of animal gametes. Autotetraploid fish (RRRR, 4nRR=200) (4nRR) were derived from the whole genome duplication of red crucian carp (RR, 2n=100) (RCC) and possessed four sets of chromosomes derived from RCC. The diploid eggs from 4nRR fish were significantly larger than those from RCC. To explore the differences between the ovaries of these two ploidies of fishes at molecular level, we compared the ovary transcriptome profiles transcriptomes of 4nRR fish and RCC and identified differentially expressed genes (DEGs). A total of 19,015 unigenes were differentially expressed between 4nRR fish and RCC, including 12,591 up-regulated and 6,424 down-regulated unigenes in 4nRR fish. Functional analyses revealed that eight genes (CDKL1, AHCY, ARHGEF3, TGFβ, Wnt11, Cyp27A, GDF7 and Ckb) were involved in the regulation of cell proliferation, cell division, gene transcription, ovary development and energy metabolism, showing eight genes were related to egg size in 4nRR fish and RCC. We validated the eight differentially expressed genes (DEGs) in 4nRR fish and RCC using quantitative PCR to quantify expression. The study results provided insights into the regulatory mechanisms that cause the differences in crucian carp egg sizes.